Differences in quality of life and cognition between the elderly and the very elderly hemodialysis patients - Viana,Fernanda Siqueira (2019)
Abstract Introduction: In the last decades, there was an expressive increase in the number of elderly patients with chronic kidney disease starting hemodialysis. Thus, our goal was to evaluate the profile of the elderly in chronic hemodialysis and to compare the cognition and quality of life of the younger elderly with those of the very elderly. Methods: Patients on hemodialysis for at least 3 months, who were 65 years of age or older when they started dialysis were invited to participate, and stratified according to age (under or over 80 years). The participants answered a clinical-epidemiological questionnaire and underwent cognitive tests (Mini Mental State Exam [MMSE], clock drawing test [CDT] and verbal fluency test [VFT]) and a quality of life assessment 36- Item Short Form Health Survey). Results: Of the 125 eligible patients, 124 agreed to participate. The mean age was 76 ± 6 years (28% ≥ 80 years), 56% were men and 55% had ≥ 8 years of schooling. Depression was suggested in 38%. The prevalence of cognitive deficit was 38%, 70% and 30%, by MEEM, CDT and VFT, respectively. The prevalence of any deficit was higher among the very elderly (94% vs. 72%, p = 0.007). Quality of life scores were similar between the two age groups, except for the functional capacity domain, worse in the group with ≥ 80 years (p = 0.033). Conclusion: Elderly patients on chronic hemodialysis have a high prevalence of cognitive deficits, especially the very elderly, but this group does not have a worse quality of life, except for functional capacity.